Selected Suites - García Lorca, Federico, 1898-1936 (Aris & Phillips Hispanic classics., 2018)
A generous selection and fresh translation of Lorca's suites, work that might have taken its place beside Songs (1927) and Poem of the Deep Song (1931) as a trilogy of Lorca's early modernist lyric. More personal than the other two works, Lorca's suites explore a 'heart without echo' in his time.